Ligand‐activated interaction of PPARδ with c‐Myc governs the tumorigenicity of breast cancer. Issue 11 (4th October 2018) - Ham, Sun Ah; Kim, Eunsu; Yoo, Taesik; Lee, Won Jin; Youn, Ju Ho; Choi, Mi‐Jung; Han, Sung Gu; Lee, Chi‐Ho; Paek, Kyung Shin; Hwang, Jung Seok; Seo, Han Geuk
Abstract : Peroxisome proliferator‐activated receptor (PPAR) δ is a promising therapeutic target in metabolic and inflammatory disorders. However, its role in oncogenesis is controversial, and its therapeutic potential remains to be determined. In our study, we show that ligand‐activated PPARδ forms a complex with the proto‐oncogene product c‐Myc. The interaction of PPARδ with c‐Myc affected the transcriptional activity of c‐Myc and the expression of its target genes. The PPARδ‐dependent regulation of c‐Myc activity was associated with decreased tumorigenicity in breast cancer cells. Administration of the PPARδ ligand GW501516 inhibited tumor growth in xenograft model mice bearing MDA‐MB‐231 cells stably expressing wild‐type PPARδ, but not those expressing dominant‐negative PPARδ, by interfering with c‐Myc function through protein–protein interaction. Our results indicating that PPARδ forms an antitumorigenic complex with c‐Myc in the presence of ligand suggest a potential role of PPARδ in breast cancer development. Abstract : What's new? Peroxisome proliferator‐activated receptor (PPAR) δ is a promising therapeutic target in metabolic and inflammatory disorders. However, its role in oncogenesis is controversial, and its therapeutic potential remains to be determined. This study shows that ligand‐activated PPARδ forms a complex with the proto‐oncogene product c‐Myc. The interaction of PPARδ with c‐Myc represses the transcriptional activity of c‐Myc and expression of its target genes. The PPARδ‐dependent regulation of c‐Myc activity is associated with decreased tumorigenicity in breast cancer cells and xenograft model mice bearing MDA‐MB‐231 cells, providing a strong mechanistic rationale for therapeutic activation of PPARδ via its non‐genomic and genomic actions.